Constellations of Disadvantage and Policy Dilemmas in Youth Transitions from School to Work in Bulgaria - Siyka Kovacheva (Social Work & Society, 2006)
In the past years there has been a growing concern in Europe with the drawbacks in youth transition from education to employment and social participation more generally (European Commission (EC) 2001; EC 2005). Bulgaria is among the countries with accumulated problems in young people's educational attainment and integration into the labour market. Having experienced a radical social transformation in the 1990s in the course of which the centrally planned and state owned economy was replaced by a market oriented one, the present-day Bulgarian society lags behind the new member states in economic output and living standards of the population. The liberalisation of social life affected young people disproportionately hard. With the state withdrawal from active interference in the regulation of relations among the social groups, young people in particular were cast from the certainty of the previously firmly structured and strictly controlled transition patterns of the state-socialist societies into the sea of the risks and uncertainties of market regulated societies (Kovacheva 2001). What are the key problems in youth school-to-work transition and main barriers of their sustainable employment integration? What are the dilemmas faced by the social inclusion policies in the country and the factors for the success and failure of the active measures in support of youth transitions?